Upaya Peningkatan Pengetahuan Low Back Pain (LBP) pada Lansia di Pos Lansia Garuda RW 26 Sibela Mojosongo - Yulia Dewi; Totok Budi Santoso (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Low Back Pain (LBP) is a problem that often occurs among Indonesian people. One of them is the community are Pos Lansia Garuda RW 26 Sibela Mojosongo. This problem often causes pain, thereby reducing the sufferer's productivity. One of the physiotherapy treatments that can be carried out is counseling which aims to increase the knowledge of members of POS LANSIA GARUDA RW 26 Sibela Mojosongo regarding Low Back Pain. With a method of providing assessment and evaluation activities that will assess the level of knowledge of participants using pretest and posttest results.